Outcomes in Hispanics With COVID‐19 Are Similar to Those of Caucasian Patients in Suburban New York. (30th October 2020) - Valenzuela, Rolando G.; Michelen, Yamil; Bracey, Alexander; Cruz, Priscilla; Fombonne, Benjamin; Fries, Bettina C.; Mallon, William K.; Fernandes, Rafael; Thode, Henry C.; Singer, Adam J.
Abstract: Background: Despite reported higher rates and worse outcomes due to COVID‐19 in certain racial and ethnic groups, much remains unknown. We explored the association between Hispanic ethnicity and outcomes in COVID‐19 patients in Long Island, New York. Methods: We conducted a retrospective cohort study of 2, 039 Hispanic and non‐Hispanic Caucasian patients testing positive for SARS‐CoV‐2 between March 7 and May 23, 2020, at a large suburban academic tertiary care hospital near New York City. We explored the association of ethnicity with need for intensive care unit (ICU), invasive mechanical ventilation (IMV), and mortality. Results: Of all patients, 1, 079 (53%) were non‐Hispanic Caucasians and 960 (47%) were Hispanic. Hispanic patients presented in higher numbers than expected for our catchment area. Compared with Caucasians, Hispanics were younger (45 years vs. 59 years), had fewer comorbidities (66% with no comorbidities vs. 40%), were less likely to have commercial insurance (35% vs. 59%), or were less likely to come from a nursing home (2% vs. 10%). In univariate comparisons, Hispanics were less likely to be admitted (37% vs. 59%) or to die (3% vs. 10%). Age, shortness of breath, congestive heart failure (CHF), coronary artery disease (CAD), hypoxemia, and presentation from nursing homes were associated with admission. Male sex and hypoxemia were associated with ICU admission. Male sex, chronic obstructive pulmonary disease, and hypoxemia were associated with IMV. Male sex, CHF, CAD, and hypoxemia were associated with mortality. After other factors were adjusted for, Hispanics were less likely to be admitted (odds ratio = 0.62, 95% confidence interval = 0.52 to 0.92) but Hispanic ethnicity was not associated with ICU admission, IMV, or mortality. Conclusions: Hispanics presented at higher rates than average for our population but outcomes among Hispanic patients with COVID‐19 were similar to those of Caucasian patients.